Science based training in elite male team handball - Wagner, H.; Ajayi, S.; von Duvillard, S. P. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Team handball is an Olympic sport game that is very popular in Europe. In most of these countries, the leading teams are managed very professionally. However, professional training in elite team handball is mostly based on practical experience because science based knowledge is lacking. Consequently, the aim of this study was to generate and perform professional training based on scientific tests in an elite male handball team. Methods: 16 (2 goal keepers and 14 field players) elite male team handball players performed a game based performance test (Wagner et al., 2014) consisting of an incremental treadmill-running test, a 30m sprinting test, lower and upper body strength test, and a counter movement jump (CMJ) test at the beginning and at the end of the first (general), at the end of the second (specific) preparation phase as well as at the end of the primary round in the Handball League Austria (HLA). We measured peak oxygen uptake (VO2peak), utilizing portable metabolic system (Cosmed K4B2), peak blood lactate concentration (BLCpeak) (EKF, Biosen C), heart rate (Polar, Kempele, Finland), sprinting time, offensive and defensive time actions (Inmotion LPM-system, Abatec, Austria), ball velocity and jump height during a jump throw (PeakMotus, Vicon Peak, UK), isometric leg force and shoulder and trunk rotation torque (ISOMED, D&R Ferstl, Germany) and jump height in the CMJ (AMTI, Watertown, USA). Based on results of the performance tests, the focus in training, adjacent to the normal team handball training, was the polarized endurance (threshold and highintensity interval) training (Stöggl et al., 2014) in the first and team handball specific coordination and endurance training in the second preparation phase and strength training during the primary round in the HLA. One-way analysis with repeated measures was used to determine the increase in performance. Results: We found a significant increase in VO2peak (P<.01) in the first and second preparation phase, in sprinting time (P<.001), offensive time (P<.001), defensive time (P<.001) and jump height in the jump throw (P<.001) in the second preparation phase as well as in the isometric leg force (P<.01) during the primary round in the HLA. It was remarkable that the increase in VO2peak was 0.8 l/min (4.1 l/min at the beginning of the first and 4.9 l/min at the end of the second preparation phase) and a decrease in the defensive time 0.6s (6.4s at the beginning of the first and 5.8s at the end of the second preparation phase). Discussion: The present study revealed that the use of scientifically based training method enables a significant increase in specific endurance and agility in elite team handball players within the preparation phase of a regular season. We propose that this combined effect of scientific tests and practical training is also appropriate to increase performance in other elite team sports.